German trade forecasts since 1970: An evaluation using the panel dimension - Christoph Behrens (Humboldt University Berlin, 2020)
I evaluate German export growth and import growth forecasts published by eight professional forecasters for the years 1971 to 2019. The focus of the evaluation is on the weak and strong efficiency as well as the unbiasedness of the forecasts. To this end, I use a novel panel-data set and estimate fixed-effects models taking into account panel-corrected standard errors. For the full time period, I find that both export and import growth forecasts are weakly but not strongly efficient. Unbiasedness depends on the forecast horizon being analyzed, with longer-term four-quarter-ahead forecasts being biased. I, furthermore, check for a possible change in forecasting behavior after incisive economic events in recent German history. I find that the strong efficiency of the forecasts did not change substantially over time. However, there is a change in forecasting behavior regarding the weak form of efficiency after the financial crisis 2008/2009.
urn:nbn:de:kobv:11-110-18452/22755-8
Keywords: C53; F17; F47; 330; Trade forecasts; German economic research institutes; Forecast Efficiency; Panel Data